1989
DOI: 10.1117/12.7977098
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Damage And The Role Of Self-Focusing

Abstract: We review the influence of self-focusing on the measurement of bulk laser-induced-damage (LID) thresholds in normally transparent optical materials. This role is experimentally determined by measuring the spot size and polarization dependence of LID and by observing beam distortion in the far field. Utilizing these techniques, we find that by using a tight focusing geometry in which the breakdown power is below P2, the effects of self-focusing can be practically eliminated in an LID experiment. P2 is the so-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 46 publications
1
45
0
Order By: Relevance
“…The NA is chosen to reduce the effects of spherical aberration, which can decrease the Strehl ratio as ablation depth is increased, 21 and to avoid self-focusing, which can cause damage before the intended focus or create a tighter focus, and lead to an underestimation of the ablation fluence threshold. 22,23 We ablate a 40 × 40 μm 2 FoV by scanning 512 lines at 1/16 frames per second, causing ∼0.078 μm separation between lines and ∼1.28 μm separation between pulses on the same line, resulting in a ∼20 pulse overlap. An FoV is ablated rather than a single point to better sample the tissue and provide a more accurate representation of l s and F th .…”
mentioning
confidence: 99%
“…The NA is chosen to reduce the effects of spherical aberration, which can decrease the Strehl ratio as ablation depth is increased, 21 and to avoid self-focusing, which can cause damage before the intended focus or create a tighter focus, and lead to an underestimation of the ablation fluence threshold. 22,23 We ablate a 40 × 40 μm 2 FoV by scanning 512 lines at 1/16 frames per second, causing ∼0.078 μm separation between lines and ∼1.28 μm separation between pulses on the same line, resulting in a ∼20 pulse overlap. An FoV is ablated rather than a single point to better sample the tissue and provide a more accurate representation of l s and F th .…”
mentioning
confidence: 99%
“…The first metric is the surface damage initiation density <N> max , and the second is the peak-irradiance in the bulk material I pk , used to predict self-focusing induced bulk filamentation damage. [36,37] These two damageability metrics are assigned failure thresholds for each downstream optic.…”
Section: Foaqual Analysismentioning
confidence: 99%
“…Optical limiting was first observed in Uquids [12]- [13] where these early experiments demonstrated that the limiting could be due to self-focusing or self-defocusing as well as absorption and scattering. Later experiments showed that semiconductors have large optical nonlmearities [24].…”
Section: Mechanisms Of Optical Limitingmentioning
confidence: 99%
“…This device regulated the output power of a continuous wave (CW) Argon ion laser. It wasn't until 1983 that CSa [13] was used as an optical limiting material for nanosecond pulses. The experiment used a focused geometry and showed that the mechanisms involved in limiting transmission were catastrophic self-focusing together with absorption and scattering resulting from laser induced breakdown.…”
Section: Introductionmentioning
confidence: 99%